Hypnotic effect of AR-001 through adenosine A1 receptor - Kim, Suyeon; Jee, Hye Jin; Park, Ju Young; Bae, Sung Hun; Kim, So Hee; Kim, Eunha; Lee, Sunghou; Jung, Yi Sook (European Journal of Pharmacology, 2024)
Insomnia is one of the most common sleep disorders, affecting 10–15% of the global population. Because classical remedies used to treat insomnia have various side effects, new therapeutics for insomnia are attracting attention. In the present study, we found that N2-Ethyl-N4-(furan-2-ylmethyl) quinazoline-2,4-diamine (AR-001) has adenosine A1 receptor agonistic activity and exhibits hypnotic efficacy by decreasing sleep onset latency and increasing total sleep time in a pentobarbital-induced sleep model. This hypnotic effect of AR-001 was significantly inhibited by the adenosine A1 receptor antagonist 8-cyclopentyl-1,3-dipropylxanthine (DPCPX). As a result of immunohistochemistry, AR-001 was shown to increase neural activity in the sleep-promoting region, ventrolateral preoptic nucleus (VLPO), and decrease neural activity in the wake-promoting region, basal forebrain (BF), and lateral hypothalamus (LH), and that these effects of AR-001 were significantly inhibited by DPCPX treatment. In addition, AR-001 increased adenosine A1 receptor mRNA levels in the hypothalamus. In conclusion, this study suggests that AR-001 has a hypnotic effect, at least partially, through adenosine A1 receptor and may have therapeutic potential for insomnia.
Keywords: Adenosine A1 Receptor Agonists; Adenosine A1 Receptor Antagonists; Animals; Furans; Hypnotics and Sedatives; Hypothalamus; Male; Mice; Pentobarbital; Quinazolines; Rats; Rats, Sprague-Dawley; Receptor, Adenosine A1; RNA, Messenger; Sleep; Sleep Initiation and Maintenance Disorders; Xanthines; Adenosine A1 receptor; Hypnotic effect; Insomnia; Sleep; Small molecule compound